The Influence of Digital Literacy Levels on Social Media Use Among Students - Irene Janeth, Gabriella; Andiyansari, Popi (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
The level of internet penetration and contribution in Indonesia is on the island of Java; the penetration rate is 81.83%, and the contribution rate is 58.51%. Of these internet users, the majority of users are university students (S1/S2). Previous research explained the influence of Facebook social media on deviant teenage behaviour (cyberbullying). The method used in this study is quantitative with a correlational approach because it demonstrates the relationship between variables. The sample of this study included 200 students from Yogyakarta. Hypothesis testing using a t-test is performed to determine the results of the predetermined hypotheses. The t-test results show that in this study, there is a significant influence between digital literacy level and social media use.